EXPLORING THE IMPACT OF 5G TECHNOLOGY ON DIGITAL TRANSFORMATION IN PROGRAMMATIC ADVERTISING - 1. Meena. N , 2. Dr. S. Kayalvizhi (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
The advent of 5G technology is set to revolutionize industries, especially digital marketing and programmatic advertising. This study explores the impact of 5G on programmatic advertising, emphasizing its potential to improve ad targeting, real-time analytics, and content delivery. With 5G’s faster speeds, lower latency, and higher bandwidth, programmatic advertising can achieve more accurate targeting, seamless integration of interactive formats like Augmented Reality (AR) and Virtual Reality (VR), and enhanced user experiences. Additionally, 5G enables advertisers to utilize artificial intelligence (AI) and machine learning for personalized, context-aware ads. Its real-time processing capabilities facilitate hyper-localized advertising, delivering tailored content based on consumers' immediate environment. However, challenges such as data privacy, security, and the ethical implications of highly personalized ads remain. This study stresses the need for ongoing research to address these challenges while maximizing the potential of 5G in reshaping the advertising landscape for a more personalized and immersive experience, while managing ethical and privacy concerns responsibly. The findings are particularly relevant to Vellore City, where local businesses and industries can benefit from the transformative potential of 5G in driving digital innovation and enhancing programmatic advertising strategies.